Rural, Regional, Racial Disparities in Telemedicine Use During the COVID-19 Pandemic Among US Adults: 2021 National Health Interview Survey (NHIS) - Park JH; Lee MJ; Tsai MH; Shih HJ; Chang J (Patient Preference and Adherence, 2023)
Jeong-Hui Park,1,* Min Jee Lee,2,* Meng-Han Tsai,3,4 Huan-Ju Shih,5 Jongwha Chang6 1Department of Health Behavior, School of Public Health, Texas A&M University, College Station, TX, USA; 2Population Science and Policy, School of Medicine, Southern Illinois University, Springfield, IL, USA; 3Georgia Prevention Institute, Augusta University, Augusta, GA, USA; 4Cancer Prevention, Control, & Population Health Program, Georgia Cancer Center, Augusta University, Augusta, GA, USA; 5Department of Health Administration and Policy, School of Public Health, George Mason University, Fairfax, VA, USA; 6Department of Pharmaceutical Sciences, Irma Lerma Rangel School of Pharmacy, Texas A&M University, College Station, TX, USA*These authors contributed equally to this workCorrespondence: Jongwha Chang, Email jc2345@tamu.eduObjective: The primary objective of this study is to conduct a comparative analysis of telemedicine utilization patterns among adult populations residing in both rural and urban areas and evaluate the probability of telemedicine adoption among adults dwelling in both rural and urban areas amid the backdrop of the COVID-19 pandemic.Methods: Our study has attained sample populations (n = 279,260, National Weighted Estimates = 2,391,188,373) through the secondary analysis of the National Health Interview Survey (NHIS) for the year 2021. We examined the relationship between the rural, regional, and racial variables using chi-square tests and binary logistic regression associated with telemedicine use in our multivariable analysis.Results: Telemedicine use by population decreased with decreasing urbanization level, from 40.2% among adults living in large central metropolitan to 29.7% among adults living in rural area (p< 0.0001). Regarding household income, adults with 400% or more of the federal poverty level (FPL) were significantly more likely to use telemedicine than adults with less than 100% of the FPL. Females were more likely than males to utilize telemedicine. In terms of region, adults living in the West were 1.25 times more likely to use telemedicine than adults living in the Northeast, and minority race/ethnicity groups (eg, Non-Hispanic Black, Hispanic, and other) are less likely to use the telemedicine rather than Non-Hispanic White.Conclusion: Health equity is attained when all demographic groups enjoy uniform access to healthcare services, but disparities emerge when there are discernible variations in access to treatment. Considering this study’s findings, it becomes evident that the distinctions in poverty rates, median income levels, and healthcare utilization patterns across racial and regional lines may serve as indicators of potential health equity concerns.Keywords: telemedicine, COVID-19, NHIS sample, healthcare utilization